Scholarly Seeking, Reading, and Use Behaviors dataset - Tenopir, Carol; Christian, Lisa; Kaufman, Jordan (Dryad, 2019)
While journal articles are still considered the most important sources of
scholarly reading, libraries may no longer have a monopoly on providing
discovery and access. Many other sources of scholarly information are
available to readers. This international study examines how researchers
discover, read, and use scholarly literature for their work. Respondents
in 2018 report an average of almost 20 article readings a month and there
are still significant differences found in the reading and use of
scholarly literature by discipline and geographical location, consistent
with the earlier studies. Researchers show they are willing to change or
adopt new strategies to discover and obtain articles.